A Decision-Making Framework for Academic Information System Maintenance Prioritization using AHP and Tiered Resource Allocation - Hilyah Magdalena; Ade Septryanti (Indonesian Journal of Information Systems, 2026)
University academic information systems face increasing digital demands, but maintenance strategies often lack systematic prioritization, leading to inefficient resource allocation and neglect of critical features. This study aims to develop a structured framework to prioritize maintenance of academic system features at ISB Atma Luhur, ensuring optimal resource distribution and system reliability. A quantitative study using the Analytic Hierarchy Process (AHP) was conducted in four phases: (1) inventorying 237 features across eight academic units and defining eight evaluation criteria through expert consultation; (2) applying AHP with 11 domain experts using Expert Choice software for criteria weighting and consistency validation (CR < 0.10); (3) calculating priority scores with PSₖ = Σ(wᵢ × sₖᵢ); and (4) designing a 24-month action plan with different resource allocations. The analysis identified two high-priority systems (BAAK: 9.14, SIAD: 8.12), three medium-priority systems (Finance: 6.85, Student Affairs: 6.79, Final Project: 6.23), and three low-priority systems (PMB: 5.18, Library: 4.12, General: 3.25). Preservation of Academic Values ​​is the most important criterion (weight: 0.258). The recommended allocation is 60% for high-priority systems, 30% for medium-priority systems, and 10% for low-priority systems. The AHP-based framework successfully achieved its objectives, providing a data-driven tool for maintenance management. Future studies should explore integration with predictive analytics to proactively improve system reliability